The effects of hot oil treatment process on the chemical, colour and strenghth properties on 15-year-old cultivated acacia hybrid - Razak Wahab; Izyan Khalid; Nurul Ain Mohd Kamal; Othman Sulaiman (2012)
The effects of hot oil treatment on the chemical, colour and strength properties of 15-year-old cultivated Acacia hybrid were investigated. Logs of A. hybrid were harvested and cut at the bottom, middle and top sections. The wood sections were treated in the hot oil treatment process using palm oil at temperatures of 180, 200 and 220°C for durations of 30, 60 and 90 min. The hot oil treatment process causes some modification in the wood features especially in the chemical constituents, colour appearances and strength properties of A. hybrid. Parameters such as temperatures and treatment time were closely monitored as they influence the chemical, colour and strength changes in the treated wood. The degradation in holocellulose, cellulose, and hemicellulose contents was recognized when acacia woods were exposed to oil thermally modified process. Holocellulose and celulose degraded with the increasing of treatment temperature and duration of heating exposure, while lignin showed the increment in content through this treatment. The colour changes in the sap and heartwood were measured using a Minolta Chroma-meter CR-310 and the results are presented in the CIE L*a*b* colour co-ordinates system. The results show that the colour of the treated sapwood can be improve to match the colour of the natural A. hybrid heartwood. The strength properties of the oil heat treated A. hybrid wood decreases in values of both MOR and MOE throughout the treatment process. The decreases in values were influenced by temperature and duration of the treatment.